Leaf Intracellular Water Transport Rate Based on Physiological Impedance: A Possible Role of Leaf Internal Retained Water in Photosynthesis and Growth of Tomatoes - Xing, Deke; Mao, Renlong; Li, Zhenyi; Wu, Yanyou; Qin, Xiaojie; Fu, Weiguo (Frontiers in Plant Science, 2022)
Water consumed by photosynthesis and growth rather than transpiration accounts for only 1%~3% of the water absorbed by roots. The leaf water transport rate (LWTR) based on physiological impedance (Z) provides information on the transport traits of the leaf internal retained water, which helps determine the intracellular water status. Solanum lycopersicum plants were subjected to five different levels of soil relative water content (SWCR) (e.g., 100%, 90%, 80%, 70% and 60%) for three months. The leaf water potential (ΨL), Z, photosynthesis, growth and water-use efficiency (WUE) were determined. A coupling model between gripping force and physiological impedance was established according to the Nernst equation, and the inherent LWTR (LWTRi) was determined. The results showed that LWTRi together with ΨL altered the intracellular water status as the water supply changed. When the SWCR was 100%, 90% and 80%, stomatal closure reduced transpiration and decreased water transport through leaves. The net photosynthetic rate (PN) was inhibited by decreased stomatal conductance (gs) or ΨL, but constant transport of intracellular water was conducive to plant growth or dry matter accumulation. Remarkably increased LWTRi helped to improve the delivery and use efficiency of the limited leaf internal water, which maintained PN and improved the WUE at 70% but could not keep the plant growth and yields at 70% and 60% due to the further decrease of water supply and ΨL. The increased transport rate of leaf internal retained water helped plants efficiently use intracellular water and maintain growth or photosynthesis, therefore adapting to the decreasing water supply. The results demonstrate the importance of transport of the leaf internal retained water in plant responses to water deficit by using electrophysiological parameters.